2018
DOI: 10.1126/sciadv.aat4779
|View full text |Cite
|
Sign up to set email alerts
|

Couples showing off: Audience promotes both male and female multimodal courtship display in a songbird

Abstract: Socially monogamous songbird couples show off their courtship display in front of other individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Such substantial sex differences in singing behaviour are commonly found in the majority of northern temperate songbird species, even though females of many tropical and southern temperate species sing regularly, and their songs play an important role in inter-sexual communication (Hall et al, 2015; Price, 2019; Price et al, 2009; Slater and Mann, 2004). For example, female blue-capped cordon-bleus ( Uraeginthus cyanocephalus ) use their song as advertising signals and address their songs to their mates (Immelmann, 1968; Ota et al, 2018), although the female songs appear shorter and less complex than those of males (Geberzahn and Gahr, 2011). In another tropical songbird species, forest weavers ( Ploceus bicolor ), males and females develop their songs during pair binding and eventually learn to sing identical duets, which they use to defend their territories (Wickler and Seibt, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Such substantial sex differences in singing behaviour are commonly found in the majority of northern temperate songbird species, even though females of many tropical and southern temperate species sing regularly, and their songs play an important role in inter-sexual communication (Hall et al, 2015; Price, 2019; Price et al, 2009; Slater and Mann, 2004). For example, female blue-capped cordon-bleus ( Uraeginthus cyanocephalus ) use their song as advertising signals and address their songs to their mates (Immelmann, 1968; Ota et al, 2018), although the female songs appear shorter and less complex than those of males (Geberzahn and Gahr, 2011). In another tropical songbird species, forest weavers ( Ploceus bicolor ), males and females develop their songs during pair binding and eventually learn to sing identical duets, which they use to defend their territories (Wickler and Seibt, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…2020) or signal their current mating status (Ota et al. 2018). To our knowledge, current work on audience effects has considered networks of only three or four individuals.…”
Section: Open Questions In the Study Of Mate Choicementioning
confidence: 99%
“…For instance, an "audience" of potential competitors can influence a chooser's preference (Plath et al 2008), or the intensity of fights among courters (Dzieweczynski et al 2005). Similarly, the presence of courters can affect chooser aggression toward conspecifics and/or heterospecifics (Makowicz et al 2020) or signal their current mating status (Ota et al 2018). To our knowledge, current work on audience effects has considered networks of only three or four individuals.…”
Section: How Does Social Context Shape Mating Preferences and Outcomes?mentioning
confidence: 99%
“…In the blue-capped cordon-bleu ( Uraeginthus cyanocephalus ; Fig. 1a ), a socially monogamous songbird, both male and female, repeatedly bob up and down and sing songs while holding a piece of nest material in the beak during courtship (Goodwin 1982 ; Ota et al 2015 , 2018 ). Using a high-speed camera, my previous laboratory study revealed that both male and female cordon-bleus rapidly stamp their feet several times in one bobbing (Ota et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%